A solid base catalyst and its application in hydrolyzing ethyl pyruvate to prepare sodium pyruvate

By using the combined technology of graded pore foam ceramics and micron aluminum powder in solid alkali catalysts, a large pore structure with high porosity and specific surface area is formed, and ZnO nanowires are grown on the pore walls, the problems of low activity and poor stability of existing solid alkali catalysts in the process of hydrolysis of ethyl pyruvate to sodium pyruvate are solved, and the improvement of efficient catalytic and mechanical properties is achieved.

CN119746843APending Publication Date: 2025-04-04苏州仁晟新材料科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411936980.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the hydrolysis of ethyl pyruvate, existing solid base catalysts have defects such as alkaline aggregation, loss, small specific surface area and poor pore structure in the process of hydrolysis of ethyl pyruvate, resulting in low catalytic activity and poor stability.

Method used

The graded pore foam ceramic is used as a support, and by adding micron aluminum powder to the silica matrix, hollow alumina spheres are formed using the Kirkendal effect to enhance the pore structure and mechanical properties of the foam ceramics, and ZnO nanowires are grown on the pore walls to improve the distribution uniformity of the active center.

Benefits of technology

It significantly improves the diffusion efficiency and catalytic activity of ethyl pyruvate, enhances the mechanical properties of foam ceramics, and improves the recyclability of the catalyst and product purity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a solid base catalyst and its application in preparing sodium pyruvate by hydrolyzing ethyl pyruvate. The preparation method is as follows: prepare silicon dioxide ceramic slurry; add micron aluminum powder and stir to mix evenly; add sodium dodecylbenzene sulfonate and cationic guar gum and stir at high speed to obtain wet foam; dry and sinter to obtain a graded pore foam ceramic body; prepare a graded pore foam ceramic body with ZnO nanowires in the pore wall; load single atomic sodium to obtain a solid base catalyst. The present invention uses graded pore foam ceramic as a carrier, which has a very large porosity and specific surface area, and greatly improves the loading amount of single atomic sodium; at the same time, micron aluminum powder is added, and the Kirkendall effect is used to oxidize the aluminum powder into hollow aluminum oxide spheres, and a graded pore structure is formed with the original foam pores at the empty wall and triangle of the foam ceramic, which is beneficial to the diffusion efficiency of ethyl pyruvate in the pore channel, making it easier for it to enter the pore channel and contact the catalytic active center, thereby improving the catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a solid base catalyst and application thereof in preparing sodium pyruvate by hydrolyzing ethyl pyruvate. Background Art

[0002] As the pollution caused by large-scale industry becomes increasingly serious, the development of environmentally friendly catalytic processes has attracted more and more attention. Solid strong bases or super strong bases as catalysts have the characteristics of high activity, high selectivity, mild reaction conditions, and easy separation of products, and are expected to become a new generation of environmentally friendly catalytic materials. Although many studies are currently focused on solid strong acids, solid super acids and even heteropoly acids, there are relatively few studies on solid bases. However, practice has proved that many chemical reactions need to be carried out in an alkaline atmosphere, especially in many fine chemical synthesis aspects. Among them, the hydrolysis of ethyl pyruvate to produce sodium pyruvate is one of them. The traditional method is that ethyl pyruvate undergoes hydrolysis in sodium hydroxide solution to generate ethanol and sodium pyruvate solution, and vacuum removes water and ethanol to obtain sodium pyruvate. However, the concentration of sodium hydroxide solution must be controlled to be less than 1%, because too high a concentration of sodium hydroxide solution will cause aldehyde-ketone condensation reaction of pyruvate, resulting in low product purity, and the later salt formation process requires evaporation of a large amount of water, resulting in excessive energy consumption costs. Therefore, it is particularly important to develop and apply solid base catalytic hydrolysis reactions. The current solid base catalysts also have some disadvantages, such as: the alkaline sites are easy to aggregate, the alkaline sites are easy to lose during the recycling process, the specific surface area is small and the pore structure is poor, the catalytic activity is low and the stability is poor, etc. Therefore, how to overcome the above defects and develop a solid base catalyst with the best effect for the hydrolysis of ethyl pyruvate to prepare sodium pyruvate is the problem to be solved by the present invention. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a solid base catalyst and its application in the hydrolysis of ethyl pyruvate to prepare sodium pyruvate, using graded pore foam ceramics as a carrier, having extremely large porosity and specific surface area, greatly improving the loading capacity of single atomic sodium; at the same time, by adding micron aluminum powder into a silica matrix, utilizing the Kirkendall effect of the micron aluminum powder, the aluminum powder is oxidized into hollow alumina spheres, and a graded pore structure is formed with the original foam pores at the empty walls and triangles of the foam ceramics, which is beneficial to the diffusion efficiency of ethyl pyruvate in the pores, making it easier for it to enter the pores and contact the catalytic active centers, thereby improving the mass transfer efficiency in the catalytic process, thereby improving the catalytic efficiency; at the same time, due to the supporting role of the hollow alumina spheres at the empty walls and triangles, the mechanical properties of the foam ceramics can also be significantly enhanced.

[0004] Technical solution: A solid base catalyst is obtained by loading single-atom sodium on graded-pore foam ceramic. The preparation method of the solid base catalyst comprises the following steps, in parts by weight: S1: 35-40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water are put into a ball mill and ball milled for 40 hours to obtain a silicon dioxide ceramic slurry; S2: Add micron aluminum powder and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate and cationic guar gum, stirring for 5-10 minutes to make them uniformly dispersed, and then stirring at high speed for 5-10 minutes to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: prepare zinc acetate solution, add an equal volume of hexamethylenetetramine, stir repeatedly for 1-2h, add graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 90-120° C. for 6-8 hours, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: prepare sodium nitrate solution, immerse the graded porous foam ceramic body with ZnO nanowires in the pore wall therein, and stir for 2-3 hours; S9: take out and dry, place in a muffle furnace, decompose and react at 400°C for 1-3 hours, heat to 800°C, and continue to react for 2-4 hours to obtain a solid base catalyst. Furthermore, in the step S1, zirconium oxide grinding balls are added during ball milling, and the ball-to-material ratio is 1:2. Furthermore, in step S2, the particle size of the micron aluminum powder is 20-70 μm, and the added amount is 10-15% of the silicon dioxide. Furthermore, in step S3, the concentration of sodium dodecylbenzene sulfonate is 0.5 g / L, and the concentration of cationic guar gum is 0.6 g / L. Furthermore, in step S3, the speed of high-speed stirring is 1000-1500 r / min. Furthermore, the concentration of the zinc acetate solution in step S6 is 0.1 mol / L. Furthermore, the concentration of the sodium nitrate solution in step S8 is 10-15%. Application of the solid base catalyst in the hydrolysis of ethyl pyruvate to prepare sodium pyruvate. Beneficial effects: 1. The present invention adopts graded pore foam ceramics as a carrier, which has extremely large porosity and specific surface area, and greatly increases the loading capacity of single atomic sodium. 2. The present invention adopts the method of adding micron aluminum powder into the silicon dioxide matrix, and utilizes the Kirkendall effect of the micron aluminum powder to oxidize the aluminum powder into hollow aluminum oxide balls, and forms a hierarchical pore structure with the original foam pores at the empty walls and triangles of the foam ceramic. This structure is beneficial to the diffusion efficiency of ethyl pyruvate in the pores, making it easier for it to enter the pores and contact the catalytic active centers, thereby improving the mass transfer efficiency in the catalytic process, thereby improving the catalytic efficiency; at the same time, due to the supporting role of the hollow aluminum oxide balls at the empty walls and triangles, the mechanical properties of the foam ceramics can also be significantly enhanced. 3. The present invention in-situ grows ZnO nanowires inside the foam ceramic. On the one hand, the introduction of ZnO nanowires can obtain ideal active center sites and reduce the aggregation of single atomic sodium. At the same time, the intricate branching structure of ZnO nanowires can also maximize the mechanical reinforcement effect of the foam ceramic. 4. The present invention uses sodium nitrate as a precursor, and undergoes two decomposition reactions at 400°C and 800°C, respectively, to eventually generate single atomic sodium. During the high-temperature calcination process, the single atomic sodium and the empty orbitals of the metal atoms of the foam ceramic combine to form shared electrons, making the connection between the two more firmly through molecular forces, thereby increasing recyclability. 5. The present invention overcomes the disadvantages of using a large amount of water (the concentration of the sodium hydroxide solution must be controlled to be less than 1%) and being prone to side reactions (pyruvate aldehyde-ketone condensation reaction) when using a traditional sodium hydroxide solution. DETAILED DESCRIPTION Example 1 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 35 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 4.55 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a hierarchical pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 2 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 3 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 4 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 4 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 6 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 5 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1000 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 6 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1500 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 7 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: pouring into a polytetrafluoroethylene autoclave, placing in an oven, heating at 90°C for 8h, washing with deionized water and drying to obtain a hierarchical pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 8 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: pouring into a polytetrafluoroethylene autoclave, placing in an oven, heating at 120° C. for 6 h, washing with deionized water and drying to obtain a hierarchical pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 13%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 9 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 10%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Example 10 A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: Prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the graded pore foam ceramic body, and stir evenly; S7: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution with a concentration of 15%, immersing the hierarchical pore foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Comparative Example 1 The difference between this embodiment and embodiment 2 is that no graded pores are formed, and porous foam is directly formed, as follows: A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S3: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S4: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a porous foam ceramic body was obtained. S5: prepare a zinc acetate solution with a concentration of 0.1 mol / L, add an equal volume of hexamethylenetetramine, stir repeatedly for 2 h, add the porous foam ceramic body, and stir evenly; S6: Pour into a polytetrafluoroethylene autoclave, put into an oven, heat at 110°C for 7h, wash with deionized water and dry to obtain a porous foam ceramic body with ZnO nanowires in the pore walls; S7: preparing a sodium nitrate solution with a concentration of 13%, immersing the porous foam ceramic body with ZnO nanowires in the pore walls therein, and stirring for 3 hours; S8: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Comparative Example 2 The difference between this embodiment and embodiment 2 is that no ZnO nanowires are generated, as follows: A method for preparing a solid base catalyst comprises the following steps, measured in parts by weight: S1: 40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water were put into a ball mill and ball milled for 40 hours. Zirconia grinding balls were added during the ball milling, and the ball-to-material ratio was 1:2 to obtain a silicon dioxide ceramic slurry; S2: Add 5.2 parts of micron aluminum powder with a particle size of 20-70 μm and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate with a concentration of 0.5 g / L and cationic guar gum with a concentration of 0.6 g / L, stirring for 8 minutes to make them uniformly dispersed, and then stirring at a high speed for 10 minutes at a rate of 1400 r / min to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: preparing a sodium nitrate solution with a concentration of 13%, immersing the graded pore foam ceramic body therein, and stirring for 3 hours; S7: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 2h, raise the temperature to 800°C, and continue the reaction for 3h to obtain a solid base catalyst. Determination of sodium single atom loading: ICP spectrometer was used to determine the sodium single atom loading; Determination of porosity: Determined in accordance with standard GB / T 1966-2024; Determination of compressive strength: According to standard GB / T 1964-2023, the test is carried out using a universal testing machine; The results are shown in Table 1 below: Table 1 Sodium single atom loading (wt.%) Porosity (%) Compressive strength(MPa) Example 1 16.29 91.6 6.79 Example 2 16.37 91.5 6.88 Example 3 15.94 90.2 6.69 Example 4 16.34 91.8 6.90 Example 5 16.28 90.7 6.93 Example 6 16.35 91.7 6.67 Example 7 16.34 91.2 6.89 Example 8 16.33 91.7 6.83 Example 9 15.20 91.6 6.88 Example 10 16.45 91.5 6.88 Comparative Example 1 15.14 87.4 6.33 Comparative Example 2 15.87 91.8 6.37 The solid base catalyst of each embodiment was applied to the hydrolysis of ethyl pyruvate to prepare sodium pyruvate. Specifically, ethyl pyruvate was added to the solid base catalyst of each embodiment and hydrolyzed to produce sodium pyruvate. The first yield was calculated by GC spectrum detection, and the purity was determined. At the same time, the yield after 4 cycles was determined. The results are shown in Table 2 below: Table 2 Initial yield (%) purity(%) Yield after 4 cycles (%) Example 2 95.2 99.9 90.9 Example 10 95.4 99.9 91.4 Comparative Example 1 90.9 99.8 83.3 Comparative Example 2 94.4 99.4 85.7 Conventional NaOH solution 80.2 99.0 -

Claims

1. A solid base catalyst, characterized in that Obtained by loading single atomic sodium on graded pore ceramic foam.

2. The method for preparing a solid base catalyst according to claim 1, characterized in that: By weight, the method comprises the following steps: S1: 35-40 parts of silicon dioxide, 1 part of sodium carboxymethyl cellulose and 100 parts of distilled water are put into a ball mill and ball milled for 40 hours to obtain a silicon dioxide ceramic slurry; S2: Add micron aluminum powder and stir to mix evenly; S3: adding sodium dodecylbenzene sulfonate and cationic guar gum, stirring for 5-10 minutes to make them uniformly dispersed, and then stirring at high speed for 5-10 minutes to obtain wet foam; S4: Cover with plastic wrap, place in an oven, dry at 35°C for 36 hours, then demould, and heat to 75°C until completely dry; S5: placing the sample in a muffle furnace, heating the sample to 1100°C at a heating rate of 10°C / min, and then keeping the temperature for 2 hours. After natural cooling, a graded pore foam ceramic body is obtained. S6: prepare zinc acetate solution, add an equal volume of hexamethylenetetramine, stir repeatedly for 1-2h, add graded pore foam ceramic body, and stir evenly; S7: pouring into a polytetrafluoroethylene autoclave, placing in an oven, heating at 90-120° C. for 6-8 hours, washing with deionized water and drying to obtain a graded pore foam ceramic body with ZnO nanowires in the pore walls; S8: preparing a sodium nitrate solution, immersing the hierarchical pore foam ceramic body having ZnO nanowires in the pore walls therein, and stirring for 2-3 hours; S9: Take out and dry, place in a muffle furnace, decompose and react at 400°C for 1-3h, raise the temperature to 800°C, and continue the reaction for 2-4h to obtain a solid base catalyst.

3. The method for preparing a solid base catalyst according to claim 2, characterized in that: In the step S1, zirconium oxide grinding balls are added during ball milling, and the ball-to-material ratio is 1:

2.

4. The method for preparing a solid base catalyst according to claim 2, characterized in that: In step S2, the particle size of the micron aluminum powder is 20-70 μm, and the added amount is 10-15% of the silicon dioxide.

5. The method for preparing a solid base catalyst according to claim 2, characterized in that: In step S3, the concentration of sodium dodecylbenzene sulfonate is 0.5 g / L, and the concentration of cationic guar gum is 0.6 g / L.

6. The method for preparing a solid base catalyst according to claim 2, characterized in that: The speed of high-speed stirring in step S3 is 1000-1500 r / min.

7. The method for preparing a solid base catalyst according to claim 2, characterized in that: The concentration of the zinc acetate solution in step S6 is 0.1 mol / L.

8. The method for preparing a solid base catalyst according to claim 2, characterized in that: The concentration of the sodium nitrate solution in step S8 is 10-15%.

9. Use of the solid base catalyst according to claim 1 in the hydrolysis of ethyl pyruvate to prepare sodium pyruvate.

Citation Information

Cited By

  • Method for synthesizing L-p-hydroxyphenylglycine methyl ester through solid alkaline catalysis

    CN121949137A